Biological Asset Disclosure in Indonesia - Aminah Aminah; Djoko Suhardjanto; Rahmawati Rahmawati; Jaka Winarna; Dea Oktaviana (Ilomata International Journal of Tax and Accounting, 2022)
The development of companies in the agricultural sector is supported by the availability of information, which is also a consideration for decision-making by company owners or company management. As a result, the company's annual report must include as much information as possible. Agricultural companies are required to disclose their biological assets under PSAK 69. However, many agricultural companies have not fully disclosed their biological assets. The focus of the research is to observe how biological assets, company growth, auditor type, and public ownership influence biological assets disclosure. Plantation & crops companies listed on the Indonesia Stock Exchange (IDX) are the population for this study, with a total of 25 entities. 13 out of 25 companies became the research sample taken using a purposive sampling method. The research technique uses panel data regression in Eviews 10. The findings of this study are biological assets intensity and auditor type have a significant positive impact on biological assets disclosure. Company growth has an insignificant positive effect on the disclosure of biological assets, public ownership has an insignificant negative effect on the disclosure of biological assets.